2019
DOI: 10.1302/0301-620x.101b3.bjj-2018-0544.r1
|View full text |Cite
|
Sign up to set email alerts
|

Medial and lateral gap laxity differential in computer-assisted kinematic total knee arthroplasty

Abstract: AimsThe results of kinematic total knee arthroplasty (KTKA) have been reported in terms of limb and component alignment parameters but not in terms of gap laxities and differentials. In kinematic alignment (KA), balance should reflect the asymmetrical balance of the normal knee, not the classic rectangular flexion and extension gaps sought with gap-balanced mechanical axis total knee arthroplasty (MATKA). This paper aims to address the following questions: 1) what factors determine coronal joint congruence as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 36 publications
6
71
0
Order By: Relevance
“…In the aMA group, the lateral gap laxity was wider than the medial gap and a wider exion gap laxity was produced, which is consistent with the ndings reported by Yoo et al in normal knee joint [38]. In addition, the lateral exion gap was signi cantly wider in the aMA group with a mean of 0.71 mm more laxity than the MA group, which matches the results of McEwen et al, who revealed a wider lateral exion gap laxity (>2 mm) was associated with better clinical and functional outcomes [39].…”
Section: Discussionsupporting
confidence: 91%
“…In the aMA group, the lateral gap laxity was wider than the medial gap and a wider exion gap laxity was produced, which is consistent with the ndings reported by Yoo et al in normal knee joint [38]. In addition, the lateral exion gap was signi cantly wider in the aMA group with a mean of 0.71 mm more laxity than the MA group, which matches the results of McEwen et al, who revealed a wider lateral exion gap laxity (>2 mm) was associated with better clinical and functional outcomes [39].…”
Section: Discussionsupporting
confidence: 91%
“…Normal gap laxities have been reported using various methods. The exion gap has been reported to be wider than the extension gap [9][10][11], and the lateral exion gap tends to be greater than the medial exion gap in normal knees [5,7,10,11,[12][13][14]. It is not known how much intraoperative ligament imbalance is permitted during TKA.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 The authors feel it is key to restore the isometric medial compartment balance/gap in extension and flexion, but some laxity (increased gap) can be tolerated in the lateral compartment, for which there is evidence of improved patient outcomes. 10 …”
mentioning
confidence: 99%